IMPLEMENTASI ARDUINO UNO UNTUK DETEKSI KEBAKARAN HUTAN - fajar; Muhammad Abrar Masril (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2023)
Forest is a gift from the Almighty God that we have to preserve, forests are very useful in the survival of humans, but due to human activity itself can damage forests such as cutting down trees wildly and burning forests to make land. The most forest fires occur from year to year, namely Indonesia resulting from forest fires will have a lot of negative impacts that occur on all living things. Therefore a forest fire detection system is needed to minimize forest fires. In this study the authors made a forest fire detection system using an Arduino-based microcontroller. The tools used are in the form of Arduino uno, Arduino mega 2560, fire sensor, MQ-7 smoke sensor and sim 800l module this tool is made so that the fire does not spread and expand. the workings of this system are when the fire and smoke sensors detect fire and smoke in the forest location, the data will be processed and directly the forested sim800l module sends sms to the sim800l module located in the office according to the number specified and the data received will produce output in the form of sirens from the buzzer, marker lights, and LCD as a description of the location of the fire. From the results of all testing tools that are made to work as expected. It can be concluded that each sensor has the maximum distance to detect smoke and fire, the sim800l module sends a message in 10 seconds, and the sound of the siren on the buzzer will live according to the conditions specified.